Analisis Mekanisme Administrasi Pengenaan Pajak Pertambahan Nilai (PPN) Wajib Pajak Badan pada Sistem Coretax oleh Kantor Konsultan Pajak Abdul Rachman - Fajar Fajar; Rudi Syaf Putra (Fakultas Ekonomi Universitas 45 Surabaya, 2025)
The Coretax Administration System is a new innovation in the field of taxation that utilizes cutting-edge technology to update and simplify the management of tax administration. It is hoped that this system will be able to unite various aspects of tax administration starting from the registration process, payment of tax obligations, submission of reports, to law enforcement into one more integrated and efficient platform. This research was conducted with the aim of examining how the VAT Management mechanism is applied to Corporate Taxpayers using the Coretax system. at the Abdul Rachman Tax Consultant Office. This study specifically highlights PT. DNG, a company that acts as a corporate taxpayer client and has been registered as a Taxable Entrepreneur (PKP). The approach used in this study is qualitative, by collecting data through direct observation, interviews, and document analysis. The findings of this study reveal that the implementation of VAT imposition administration by PT. DNG through the Coretax system at the Abdul Rachman Tax Consultant Office runs smoothly and is consistent with applicable tax regulations. The use of the Coretax system significantly simplifies the tax administration workflow, starting from entering the account of the person in charge (PIC), the process of creating and uploading invoices, reporting Periodic Tax Returns, to completing VAT payments.